Guided imagery and progressive muscle relaxation as a cluster of symptoms management intervention in patients receiving chemotherapy: A randomized control trial - Charalambous, Andreas; Giannakopoulou, Margarita; Bozas, Evangelos; Marcou, Yiola; Kitsios, Petros; Paikousis, Lefkios (My University, 2016)
This is anObjective: Patients receiving chemotherapy often experience many different symptoms that can be difficult to alleviate and ultimately negatively influence their quality of life. Such symptoms include pain, fatigue, nausea, vomiting and retching, anxiety and depression. There is a gap in the relevant literature on the effectiveness of cognitive-behavioural and relaxation techniques in symptom clusters. The study reflects this gap in the literature and aimed to test the effectiveness of Guided Imagery (GI) and Progressive Muscle Relaxation (PMR) on a cluster of symptoms experienced by patients undergoing chemotherapy. Methods: This was a randomized control trial with 208 patients equally assigned either in the intervention or the control group. Measurements in both groups were collected at baseline and at completion of intervention (4 weeks). Patients were assessed for pain, fatigue, nausea, vomiting and retching, anxiety and depression. The overall management of the cluster was also assessed based on the patients' self-reported health related quality of life-HRQoL. Chisquare tests (X2), independent T-tests and Linear Mixed Models were calculated. Results: Patients in the intervention group experienced lower levels of Fatigue (p <0.0.0225), and Pain (p = 0.0003) compared to those in the control group and experienced better HRQoL (p <0.0001) [PRE-POST: Intervention: Pain 4.2(2.5) - 2.5(1.6), Fatigue 27.6(4.1) - 19.3(4.1), HRQoL 54.9(22.7) - 64.5(23), Control: Pain 3.5(1.7) - 4.8(1.5), Fatigue 28.7(4.1) - 32.5(3.8), HRQoL 51.9(22.3)- 41.2(24.1)]. Nausea, vomiting and retching occurred significantly less often in the intervention group [pre-post: 25.4(5.9)- 20.6(5.6) compared to the control group (17.8(6.5)- 22.7(5.3) (F = 58.50 p <0.0001). More patients in the control group (pre:n = 33- post:n = 47) were found to be moderately depressed compared to those in the intervention group (pre:n = 35-post:n = 15) (X2 = 5.93; p = 0.02). Conclusion: This study provided evidence that the combination of GI and PMR can be effective in the management of a cluster of symptoms in cancer patients receiving chemotherapy. These techniques can complement existing management measures to achieve a comprehensive management of this symptom cluster and increase patients HRQoL.
Keywords: Chemotherapy; Patients